Dynamic affinity chromatography in the separation of sulfated lignins binding to thrombin - Liang, Aiye (2012)
Sulfated low molecular weight lignins (LMWLs), a mixture of chemo-enzymatically prepared oligomers, have been found to be potent antagonists of coagulation. However, structures that induce anticoagulation remain unidentified. The highly polar sulfate groups on these molecules and the thousands of different structures present in these mixtures make traditional chromatographic resolution of sulfated LMWLs difficult. We performed dynamic thrombin affinity chromatography monitored using chromogenic substrate hydrolysis assay to isolate sulfated LMWL fractions that differed significantly in their biophysical and biochemical properties. Three fractions, I(35), I(55) and Peak II, were isolated from the starting complex mixture. Independent plasma clotting assays suggested that I(35) possessed good anticoagulation potential (APTT = 4.2 μM; PT = 6.8 μM), while I(55) and Peak II were approximately 10- and 100-fold less potent. The ESI-MS spectrum of this oligomeric fraction showed multiple peaks at 684.8, 610.6, 557.4, 541.4, 536.5, and 519.4 m/z, which most probably arise from variably functionalized (β-O4—β-β-linked trimers and/or a β-O4—β-O4-linked dimers. The first direct observation of these structures in sulfated LMWLs will greatly assist in the discovery of more potent sulfated LMWL-based anticoagulants.